(untitled) (Research, Society and Development, 2021)
Cúrcuma longa belongs to the Zingiberaceae family, popularly known as turmeric, turmeric, yellow ginger and sun root. Consumed mainly in the form of dry powder, used for several purposes, mainly in traditional and modern medicine. As a consequence of its high commercial value, turmeric has often been adulterated with the most diverse materials and strategies. In this sense, the objective of this work was to analyze possible adulterations in samples of turmeric powder sold in the cities of Campina Grande and Pocinhos in Paraíba. For this, the starch activation and lugol reaction tests were carried out on 10 samples acquired at different commercial points in the cities mentioned. In the starch activation test, only one sample resulted in a full-bodied solution indicating the presence of starch. In the lugol reaction test, 4 samples showed a dark blue / violet color that indicates the presence of starch. It was observed that adulteration was found in a higher percentage in samples sold in open markets. In view of the results, it is observed that the detection of adulterants thus becomes an issue of high importance to ensure consumer protection against fraudulent practices. Thus, it is concluded that the results of this work revealed fraud in some samples and highlights the importance of adopting control and inspection measures to prevent economic losses and risks to consumer health.